Identification and Characterization of a Cellulase-Encoding Gene from the Buffalo Rumen Metagenomic Library - Nhung Hong NGUYEN; Lalita MARUSET; Tanaporn UENGWETWANIT; Wuttichai MHUANTONG; Piyanun HARNPICHARNCHAI; Verawat CHAMPREDA; Sutipa TANAPONGPIPAT; Kanya JIRAJAROENRAT; Sudip K. RAKSHIT; Lily EURWILAICHITR; Somchai PONGPATTANAKITSHOTE (My University, 2012)
Microorganisms residing in the rumens of cattle represent a rich source of lignocellulose-degrading enzymes, since their diet consists of plant-based materials that are high in cellulose and hemicellulose. In this study, a metagenomic library was constructed from buffalo rumen contents using pCC1FOS fosmid vector. Ninety-three clones from the pooled library of approximately 10,000 clones showed degrading activity against AZCL-HE-Cellulose, whereas four other clones showed activity against AZCL-Xylan. Contig analysis of pyrosequencing data derived from the selected strongly positive clones revealed 15 ORFs that were closely related to lignocellulose–degrading enzymes belonging to several glycosyl hydrolase families. Glycosyl hydrolase family 5 (GHF5) was the most abundant glycosyl hydrolase found, and a majority of the GHF5s in our metagenomes were closely related to several ruminal bacteria, especially ones from other buffalo rumen metagenomes. Characterization of BT-01, a selected clone with highest cellulase activity from the primary plate screening assay, revealed a cellulase encoding gene with optimal working conditions at pH 5.5 at 50 °C. Along with its stability over acidic pH, the capability efficiently to hydrolyze cellulose in feed for broiler chickens, as exhibited in an in vitro digestibility test, suggests that BT-01 has potential application as a feed supplement.
Keywords: Fosmid; Hydrolase; Fibrobacter succinogenes; Biofuel production and bioconversion